2016
DOI: 10.1007/s00240-016-0858-9
|View full text |Cite
|
Sign up to set email alerts
|

Stone culture retrieved during percutaneous nephrolithotomy: is it clinically relevant?

Abstract: Stone culture has been frequently investigated following percutaneous nephrolithotomy (PNL) in the last decade. We aimed to crucially define the clinical role of stone culture in modifying the treatment plan in patients with postoperative sepsis. Between June 2012 and April 2013, a total of 79 consecutive PNL procedures were included. Perioperative data were prospectively maintained. Preoperative urine sample, retrieved stone fragments and postoperative nephrostomy tube urine sample were cultured and antibioti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Our rate of antibiotic switching (20.7%) confirmed the clinical utility of SC. On the contrary, Osman et al reported that SC was clinically useful only in 1 patient with positive SC [25]. Despite a similar rate of SC positivity (28% in our series vs 29.1%), we included more patients (107 vs 79) and a greater number of stone variables.…”
Section: Discussionmentioning
confidence: 61%
“…Our rate of antibiotic switching (20.7%) confirmed the clinical utility of SC. On the contrary, Osman et al reported that SC was clinically useful only in 1 patient with positive SC [25]. Despite a similar rate of SC positivity (28% in our series vs 29.1%), we included more patients (107 vs 79) and a greater number of stone variables.…”
Section: Discussionmentioning
confidence: 61%
“…Previous studies reported that an incidence of septic shock (1.09%) was noted in patients with negative preoperative UC 13 , which indicated that patients with negative UC were still at risk of serious infection complications after surgery. It has been reported that calculi and intraoperative UC are better than preoperative UC in predicting the occurrence of postoperative infection complications 10 , 11 , 14 . However, infection complications generally occur within 24 h after surgery, and stones and an intraoperative urine culture cannot provide early warning for clinicians to prevent postoperative infectious complications.…”
Section: Introductionmentioning
confidence: 99%
“…Postoperative calculi culture is not routinely performed in stone surgery cases, previous studies revealed the diverse result. Five studies encourage routine calculi culture examination (Songra et al, 2015;Martov et al, 2014;Gupta et al, 2020;Ashra Mahabani & Kumar, 2022), but two studies suggest the opposite (Osman et al, 2016;Elshal et al, 2014). Songra et al (2015), and Gupta et al (2020) showed the relevancy of calculi culture in urological procedures, but the included cases were all preoperative urine culture status, positive and negative.…”
Section: Introductionmentioning
confidence: 99%